A New Scale for Evaluating the Risks for In-Hospital Falls of Newborn Infants: A Failure Modes and Effects Analysis Study - Faruk Abike; Sinan Tiras; İlkkan Dünder; Ayfer Bahtiyar; Ozlem Akturk Uzun; Ozlusen Demircan (International Journal of Pediatrics)
We aimed to develop a new scale for evaluating risks and preventive measures for in-hospital falls of newborn infants, from admission to discharge of the expectant mother. Our study was prepared in accordance with Failure Modes and Effects Analysis criteria. The risks and preventive measures for in-hospital falls of newborns were determined. Risk Priority Numbers (RPNs) were determined by multiplication of the scores of severity, probability of occurrence, and probability of detection. Analyses showed that risks having the highest RPNs were the mother with epidural anesthesia (RPN: 350 point), holding of the baby at the moment of delivery (RPN: 240), and transportation of baby right after delivery (RPN: 240). A reduction was detected in all RPNs after the application of preventive measures. Our risk model can function as a guide for obstetric clinics that need to form strategies to prevent newborn falls.